Pharmacies During COVID-19: Implementing Protective Measures For Everyone - ouelkabir, soufiane; brahmi, chaimae; karroum, abdessamad; maska, hamza; enneffah, wafaa; derraji, soufiane (Universitas Airlangga, 2025)
The COVID-19 pandemic prompted health authorities to adopt measures to protect the population by curbing the spread of the virus. Given that SARS-CoV-2 is primarily transmitted through close contact with infected droplets, aerosols, or contaminated surfaces, the measures implemented include social distancing, adherence to hand hygiene rules, and vaccination of the population. To assess compliance with anti-COVID-19 barrier measures implemented by dispensing pharmacists after the pandemic, we conducted a descriptive cross-sectional study. The study included 117 dispensing pharmacists, 74% of whom practiced in urban areas. The results of our research show that anti-COVID-19 barrier measures in pharmacies are partially maintained at 74%. The use of glass barriers over countertops is at the top of the list, at 71%, followed by hand disinfection with hydroalcoholic gel after each user visit, at 27%. Other measures, such as the wearing of masks, the presence of a hydroalcoholic gel dispenser at the entrance, limiting the number of users in the pharmacy, as well as the indication of one-way traffic and physical distance lines on the floor, are applied at rates of 1%, 6%, 3% and 4% respectively. Our study also revealed that 45% of dispensing pharmacists support maintaining or extending anti-COVID-19 barrier measures in their pharmacies. It is essential to note that although working in a pharmacy requires close interaction with users, maintaining distancing and hand hygiene measures remains crucial for reducing the risk of infectious disease transmission, thereby promoting a safe and healthy environment for both pharmacy staff and users.